ASSESSMENT OF QUALITATIVE CHARACTERISTICS OF NONPRESTRESSED REINFORCEMENT OF GRADE S500 ACCORDING TO STB 1704–2012 IN VIEW OF THE MAIN EUROPEAN NORMS - T. A. Akhmetov; Ya. V. Chikishev; I. N. Radkova; L. V. Loktionova (Литьë и металлургия)
It is offered to make additions to STB 1704-2014 with regard to requirements to strength and plastic properties that will enable to make this standard correspond the European norms. Therefore it is necessary to introduce in STB 1704-2012 several grades of reinforcing steel with various plasticity rates without limitation in the way of production.